2014
DOI: 10.1111/chd.12200
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms in Patients with Congenital Heart Disease: Incidence and Prognostic Value of Self-Rating Depression Scales

Abstract: The incidence of depressive symptomatology in patients with CHD is rather high and is associated with poorer prognosis. The BDI seems to independently predict adverse clinical outcome. Standardized screening tools and psychosocial interventions to improve the well being of these patients should be a priority in the overall care of this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…20 There is also preliminary evidence to suggest that depressive symptoms in adolescents and adults with CHD contribute to poorer clinical cardiac outcomes. 21 However, even in the absence of any link between psychological and medical outcomes, clinical attention to the psychological needs of adults with CHD would be warranted in order to optimize quality of life. 22,23 Our collective responsibility to managing adults with CHD goes beyond reducing cardiac mortality and morbidity.…”
Section: Psychological Distress Among Adults With Chdmentioning
confidence: 99%
“…20 There is also preliminary evidence to suggest that depressive symptoms in adolescents and adults with CHD contribute to poorer clinical cardiac outcomes. 21 However, even in the absence of any link between psychological and medical outcomes, clinical attention to the psychological needs of adults with CHD would be warranted in order to optimize quality of life. 22,23 Our collective responsibility to managing adults with CHD goes beyond reducing cardiac mortality and morbidity.…”
Section: Psychological Distress Among Adults With Chdmentioning
confidence: 99%
“…A recent Finnish longitudinal developmental study spanning preschool measurement with adulthood indicated that trajectories of steep increases in triglycerides were predictive of depression onset [29]. One prospective study in congenital heart disease for major adverse cardiovascular events (fatal and hospitalization incidences) related to depression indicated ORs 1.6–3.6 for a 5-year period [30]. The cross-sectional fatal SCORE risk in a Finnish regional study for depression was OR 2.9 for males and OR 1.3 for females with 30% of MetS prevalence [31].…”
Section: Discussionmentioning
confidence: 99%
“…Findings on the frequency and severity of current anxiety-depressive symptoms assessed by self-report are mixed. Some studies found high symptomatology in adults with CHD (59, 61, 6365), whereas others did not (6672). According to several authors (60, 7174), denial mechanisms or coping strategies are frequently used by CHD patients and could contribute to the favorable psychological outcomes sometimes suggested by self-assessments.…”
Section: Adults With D-tga: Emerging Evidencementioning
confidence: 99%
“…Other studies report that only 11–12% of patients receive psychological counseling, despite high rates of anxiety-depressive syndromes (62, 64). In adults with CHD, presence of a high depressive or anxiety symptomatology is associated with higher rates of unemployment (64), lower quality of life (QoL) (62, 64, 68), greater consumption of tobacco and alcohol (75), poorer adherence to treatment (76), and worse cardiac prognosis (65). …”
Section: Adults With D-tga: Emerging Evidencementioning
confidence: 99%